Graphene oxide/polyvinylpyrrolidone-doped MoO3 nanocomposites used for dye degradation and their antibacterial activity: a molecular docking analysis - Ikram, Muhammad; Atiq, Iram; Rafiq Butt, Alvina; shahzadi, Iram; Ul-Hamid, Anwar; Haider, Ali; Nabgan, Walid; Medina, Francisco (Frontiers in Chemistry, 2023)
In this study, MoO3 nanostructures (NSs) were prepared; doped with various concentrations of graphene oxide (2, 4% GO) and a fixed amount of polyvinylpyrrolidone (PVP) using the co-precipitation method. The purpose of this study is to remove organic contaminants from industrial water and evaluation of bactericidal behaviour. Introducing polymer (PVP) to metal oxides results in beneficial properties owing to reduced toxicity of metal oxides. Catalytic activity (CA) was performed against RhB by (2, 4%) GO/PVP-MoO3. Moreover, GO/PVP doped MoO3 showed good bactericidal potential results against E.coli owing to GO producing more reactive oxygen species (ROS). Furthermore, insilico docking revealed the possible inhibitory impact of synthesized nanocomposites on the folate and fatty acid synthesis enzymes DHFR and FabI, respectively.